Inpatient service utilization amongst infants diagnosed with Respiratory Syncytial Virus infection (RSV) in the United States - Jason R. Gantenberg; Kathryn D. Thompson; Robertus van Aalst; David M. Smith; Megan Richards; Christopher B. Nelson; William V. La Via; Sandra S. Chaves; Angela M. Bengtson; David A. Savitz; Andrew R. Zullo (PLoS ONE, 2025)
Introduction Respiratory syncytial virus (RSV) is the leading cause of hospitalization among US infants. Characterizing service utilization during infant RSV hospitalizations may provide important information for prioritizing resources and interventions. Objective The objective of this study was to describe the procedures and services received by infants hospitalized during their first RSV episode in their first RSV season, in addition to what proportion of infants died during this hospitalization. Methods In this retrospective observational study, we analyzed three different administrative claims datasets to examine healthcare service utilization during RSV hospitalizations among infants. The study population included infants born between July 2016 and February 2020 who experienced an RSV episode during their first RSV season and had an associated inpatient hospitalization. We stratified infants into three comorbidity groups: healthy term, palivizumab-eligible, and other comorbidities. Outcomes included extracorporeal membrane oxygenation, supplemental oxygen use (in-hospital and post-discharge), mechanical ventilation (invasive and non-invasive), chest imaging, infant mortality, length of inpatient stay, intensive care unit (ICU) admission, and number of days in the ICU. Results Chest imaging was the most frequently administered procedure during RSV-associated hospitalizations, with approximately 34–38% of infants receiving it. Around one-quarter of infants were admitted to the ICU during their first RSV hospitalization. Median lengths of stay in the hospital were 3–4 days, extending to 4–6 days in the presence of ICU admission. Palivizumab-eligible infants had higher utilization of healthcare services and spent more time in the hospital or ICU compared to healthy infants or those with other comorbidities. Conclusions This study provides insights into the utilization of healthcare services during RSV hospitalizations among infants. Understanding service utilization patterns can aid in improved management and resource allocation for infants in the United States, ultimately contributing to better outcomes and reduced healthcare costs overall. However, likely under-ascertainment of ventilation and oxygen-related services in insurance claims remains an impediment to studying these outcomes.